(untitled) (Моделювання, керування та інформаційні технології, 2025)
The authors’ research concerns the equations of filtration of contaminated water with dispersed particles of organic residues. A review of works, formulation of research tasks and a mathematical model of filtration with consideration of clogging and suffusion processes and biodegradation are carried out. Dependencies for estimating the volume of greenhouse gases released as a result of biodegradation of organic pollution are proposed. Дослідження авторів стосуються рівнянь фільтрації забрудненої води з дисперсними частинками органічних решток. Проведено огляд робіт, постановку задач дослідження та побудовано математичну модель фільтрації з урахуванням кольмотаційно-суфозійних процесів та процесів біодеградації.